Expert Systems : A Literature Review - Amba, S. (Journal of Information and Knowledge, 1988)
Scope of the review - This review covers (i) the literature published in 1985, 1986 and 1987. It is, however, not a comprehensive review. However, two papers published in 1983 and 1984 (8 and 41) have been included as it was felt that they would be of interest. (ii) It covers only library and information science literature. The secondary sources used were Library Literature and Library and Information Science Abstracts. (iii) It does not include descriptions of commercial software packages.